Significance of Immunohistochemistry in Accurate Characterisation of Hodgkin Lymphoma (Journal of Enam Medical College, 2015)
Background: Hodgkin lymphomas are malignant disorders of cells residing in lymphoid tissue and containing Reed-Sternberg (RS) cells and its variants and account for about 0.7% of all new cancers. Hodgkin lymphomas are two types: Classical Hodgkin lymphoma (CHL) that is CD30 positive and CD45 negative in specific pattern; Lymphocyte-predominant Hodgkin lymphoma (LPHL) that is CD30 negative and CD45 positive in specific pattern. Objective: To evaluate the value of immunohistochemistry in the diagnosis and accurate characterisation of Hodgkin lymphoma. Materials and Methods: This cross-sectional study was carried out in the department of Pathology of Sir Salimullah Medical College & Mitford Hospital, Dhaka from January 2010 to June 2012. Histopathologically diagnosed 45 cases of Hodgkin lymphoma and 5 cases of other than Hodgkin lymphoma were selected and then immunomarkers CD30 and CD45 were applied. Results: Among 50 cases 37 were classical Hodgkin lymphoma and 8 cases were lymphocytepredominant Hodgkin lymphoma histopathologically. When immunomarkers were applied in 50 cases then 33 cases were classical Hodgkin lymphoma and 9 cases were lymphocyte-predominant Hodgkin lymphoma. Conclusion: Immunohistochemistry helped in accurate characterisation of Hodgkin lymphoma. DOI: http://dx.doi.org/10.3329/jemc.v5i1.21493 J Enam Med Col 2015; 5(1): 23-29